PENGEMBANGAN BUDAYA MUTU MADRASAH - Akhmad Munir (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2016)
Culture quality is a value system organization which has constructed a con-dusively environment for creating and improving a quality continuously. It consist of philosophy, believe, attitude, norm, tradition, procedur, and ex-pectation. Hence, to increase culture quality in school, the strategies mana-gement is needed. So, the culture quality that reflected will be covered to all aspect and lead quality achievement in totality. This study conducted using qualitative approach within case study descriptive model. Sampling techniques were also conducted using interview, obser-vation and documentation. Data analysis including reduction, imaging and conclusion were analyzed. Validity performed using dependability and con-firmability Participation Action Research (PAR) Extention. Triangulation techniques were conducted using a variety of sources, theories, and me-thods, as well as the persistence of observations. The informants included: school principals, heads of administration, curriculum, quality assurance, public relations, religious, and also facilities and infrastructure. The finding of this study showed that culture quality of Madrasah Aliyah Negeri (MAN) 3 Malang were formed in line with the dynamics of the school change and development from time to time, either related to a change of leadership and institutional management. At this point, the riptide of MAN 3 Malang gave an impact on the academic community, both mentally and morally psychological as well as physiological. However, since it is based with a strong commitment, hard work and rely on the noble values and ideals of the institution in educating for the next generation, so that MAN 3 Malang got many achievements and continue to be maintained and developed so that it becomes a culture for the entire academic community in achievement. Furthermore, there is a great idea and a very brilliant effort which is undertaken by the academic community MAN 3 Malang from time to time in creating the culture of quality.